Climate change impacts of the UK Foreign, Commonwealth & Development Office (FCDO) commercial agriculture portfolio - Costa, Ciniro; Dittmer, Kyle M; Oliveira Quintana, Gabriel de; Shelton, Sadie W.; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This report provides an initial, rapid assessment of a selection of programmes in the commercial agricultural portfolio of the Department for International Development of the United Kingdom (DfID) (now the Foreign, Commonwealth and Development Offices or FCDO) to demonstrate a range of interventions and their likely net greenhouse gas (GHG) emission impacts. Analysis of crop and livestock value chains in seven countries, representing over four million hectares, shows that the changes in farmers’ practices supported by DfID’s bilateral investments in commercial agriculture significantly enhance crop and livestock production, while likely reducing net GHG emissions in the near term. The programme value chains increased average crop productivity by 1.0 ton per hectare per year (t ha-1 y-1), and reduced net GHG emissions by as much as 5.5 tCO2e ha-1 y-1 (cocoa agroforestry) compared to the start of the programme. Cereals demonstrated smaller annual changes, averaging a reduction of 0.80 tCO2e ha-1 y-1. Livestock productivity only increased slightly on average from 1.0 (goats) to 3.0 kg head-1 y-1 (beef cattle), with corresponding slight reductions in net GHG emissions from 0.001 (goats) to 0.01 (beef cattle) tCO2e head-1 y-1. Increases in emissions across the programmes are commonly due to increased use of nitrogen fertiliser and mechanisation. Reductions are commonly due to carbon sequestration in the soil as a result of manure addition, minimum tillage, crop rotation or reduced burning. These results are consistent with the increased use of inputs expected from market-driven agricultural intensification.